Implementasi Edukasi Smart Parenting dan Pemberian Makan Tambahan Plus Sebagai Intervensi Pencegahan Stunting - Nur Lailyanna Bisri; Moh Anang Abidin (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2024)
The stunting is a condition of growth failure experienced by children, especially at the age of under 6 years. Failure to thrive means there is disorientation in physical growth that is disproportionate between age and height. Whereas developmental failure is more related to failure in mental function, namely cognitive, psychomotor and affective dimensions. The research design used was a cross-sectional study. Namely an observational study that analyzes variable data collected at a certain point in time across a predetermined sample population or subset. This research was conducted in the working area of Krembung District, Sidoarjo Regency in January-December 2022 where this area is one of the areas with stunting that is almost evenly distributed in every village. The population in this study were all toddlers in the working area of Krembung District, Sidoarjo Regency, consisting of 19 villages. The results of the study, namely that during a span of approximately one year a sensitive intervention program on the prevention and handling of stunting was carried out in the Krembung Subdistrict working area showed that out of 3275 toddlers measured, there were 4.90% or around 151 toddlers stunting, namely where 1.70% toddlers 'very short' and 2.80% 'short' and 0.40 are categorized as BGM (Below the Red Line).